PENGARUH KEPEMIMPINAN CAMAT KELENGKAPAN SARANA DAN KOMUNIKASI ORGANISASI TERHADAP EFEKTIVITAS PELAYANAN PUBLIK DI KECAMATAN PINANG KOTA TANGERANG - Kusnadi, Rudi; Eliadi , Dafyar; Darmojo, Hardjito S.; Mulyadi, Edi (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2024)
The objectives to be achieved from this study are to determine the influence of sub-district leadership, completeness of facilities and organizational communication on the effectiveness of public services in Pinang District, Tangerang City. The population used as the object of the study were employees of Pinang District, Tangerang City. The results of the study: (1) the influence of sub-district leadership on the effectiveness of public services obtained a positive correlation value of 0.881 with a very strong relationship, the significance test of t count (2.420) > t table (1.685). This means that sub-district leadership partially has a positive and significant effect on the effectiveness of public services in Pinang District, Tangerang City; (2) the influence of completeness of facilities on the effectiveness of public services obtained a positive correlation value of 0.875 with a very strong relationship, the significance test of t count (2.536) > t table (1.685). This means that completeness of facilities partially has a positive and significant effect on the effectiveness of public services in Pinang District, Tangerang City; (3) the influence of organizational communication on the effectiveness of public services obtained a positive correlation value of 0.836 with a very strong relationship, the significance test of t count (4.386) > t table (1.685). This means that organizational communication partially has a positive and significant effect on the effectiveness of public services in Pinang District, Tangerang City; (4) the influence of sub-district leadership, completeness of facilities and organizational communication on the effectiveness of public services obtained a positive correlation value of 0.937 with a very strong relationship, the significance test of significant value F count (89.436) > F table (3.25). This means that sub-district leadership, completeness of facilities and organizational communication together have an effect on the effectiveness of public services in Pinang District, Tangerang City. Keywords: Sub-district Head Leadership, Completeness of Facilities, Organizational Communication and Effectiveness of Public Services.